The possibility of talent identification in the footballs and talent transfer from the footballs - Yamashita, S. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Performance level has consistently improved in elite sports. Under such circumstances, the quality of Talent Identification and Development (TID) program has become one of the critical factors for success in elite sport such as Olympic Games / World Championships. It is important to develop the system that enables to identify and develop athletes with the potential to achieve world class success. Discussion The football and rugby players have attracted the attention as excellent resources for talent transfer. For example, UK Sport has implemented TID program targeting the football and rugby players who could not reach to be professional (i.e., Pitch2Podium). This program creates another opportunity for young football and rugby players to challenge for success in new olympic sports. In Vancouver Olympic Games, a rugby player, Heather Moyse, won the gold medal in Bobsleigh. She played for the Canadian National team at 2006 and 2010 Women`s Rugby World Cup (WRWC). These examples shows the possibility of talent transfer in rugby. Although the women`s sevens rugby will be an Olympic sport from 2016, the number of athletes in women`s rugby is still limited in all over the world. In turn, the talent pool for women`s rugby is yet small. Thus, TID programs targeting Rio 2016 might be one of the critical success factors in women`s rugby. Conclusion In football, it become important to develop the system that enables to identify athletes with the potential to achieve world class success.